(untitled) (Raparin Journal of Humanities (RJH), 2025)
The main argument of the research is that the problem of governance in the Kurdistan Region lies in the issue of institutions. It is the institutions that motivate and encourage citizens to participate in political and economic activities or prevent and discourage them. It is the institutions that cause wealth and happiness (institutional conditions) for officials or poverty and misery for citizens to access to opportunities and services (institutional opportunities). Acemoglu and Robinson (2012) narrating the history of institutions, how and when institutions move towards closure or opening, which is obviously not an inevitable path. A nation may be rich in the past, but because of a historical event it may become poor, and vice versa. This study looks at the issue of institutions in the Kurdistan Region from the perspective of historical institutionalism as a qualitative method and provides an institutional analysis. One of the most important consequences is that the institutions have taken a path that has brought happiness and prosperity to political and family elites and those who support them. On the contrary, the majority of Kurdistan people wish for the life they live such as prosperity and wealth in necessities of life and services.